2003
DOI: 10.1103/physrevlett.91.137204
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic Phase Transitions and Spin Wave Excitations in a Ferromagnetic Stripe

Abstract: Magnetic excitations of micrometer-wide ferromagnetic stripes subjected to a transverse applied field have been measured between 1 and 20 GHz. The complexity of the observed response is attributed to the spatially nonuniform equilibrium spin distribution. This one is modeled analytically and numerically, which allows one to distinguish two micromagnetic phases governing the ground state. The nucleation-related phase transitions are evidenced by soft modes, while the different observed resonances are attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…Due to the shape anisotropy, the magnetization at the edges is pinned along the long axis of the Py stripe, while the magnetization towards the center of the stripe tends to align with the external bias field. This creates a varying magnetization profile across the width of the stripe [34], which has been used to explain that the spin wave dispersion relation changes as a function of position [25,33,35]. Due to the varying demagnetizing field profile and stronger exchange interaction effects at the edges [32,34], a weaker effective field exists at the edges as compared to the center of the stripe and as a result, the frequencies of the edge mode are lower than that of the center mode.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…Due to the shape anisotropy, the magnetization at the edges is pinned along the long axis of the Py stripe, while the magnetization towards the center of the stripe tends to align with the external bias field. This creates a varying magnetization profile across the width of the stripe [34], which has been used to explain that the spin wave dispersion relation changes as a function of position [25,33,35]. Due to the varying demagnetizing field profile and stronger exchange interaction effects at the edges [32,34], a weaker effective field exists at the edges as compared to the center of the stripe and as a result, the frequencies of the edge mode are lower than that of the center mode.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…Micromagnetic simulations and experimental evidences have shown that, in the case of transversally magnetized micron-sized permalloy stripes, the equilibrium magnetization configurations include zones near the edges of the stripes with a large component of the magnetization parallel to the axis of the stripes. 16,17,[26][27][28][29] The eventual presence of these not fully saturated zones near the edges of the stripes could possibly reduce the transverse dipolar fields involved in the resonance conditions, thus giving rise to a decrease of the resonance field of the stripes. It is important to note that, although the resonances occur after the wires have reached saturation, as indicated by the dotted lines in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the spin-wave quantization effect in patterned magnetic thin films [1,2] many works focused on the research of eigen-excitations in magnetic media with a reduced dimensionality. The amplitude profile, the discrete frequencies and the quantization conditions of spin-wave eigenmodes in stripes [1,2,3,4], rectangles [4,5], disks and ellipses [6,7] are now well understood and allow nowadays even for an engineering of the spin-wave eigenmode spectrum in such a small magnetic structure taking into account issues of geometric shape, multilayer stacks, and even magnetic domain structure.…”
Section: Introductionmentioning
confidence: 99%